Efektivitas Kebijakan Work-Life Balance Pada Karyawan PT. Indomarco Prismatama Palembang - Itryah, Itryah; Agustia, Lissa (Universitas Pahlawan Tuanku Tambusai, 2025)
Performance is important for a company or organization because the high performance of employees can affect the running of the company or organization, while work-life balance is a reference to individual involvement and satisfaction of their roles in work life and personal life without conflict between the two roles. Therefore, companies are expected to pay attention to job satisfaction and psychological needs, namely work-life balance in supporting employee performance. This study aims to determine the effect of work-life balance on employee performance. The methods used in this research are interviews and observations. The results showed that work interferance with personal life, personal life interferance with work, work life enhancement, and personal life enhancement had a significant effect on job satisfaction in employees at PT Indomarco Prismatama Palembang that employees' responsibilities at work did not make employees lose their personal lives as well as personal life did not make them forget their responsibilities as workers even work can make employees feel happy and satisfied with their lives and personal life can increase their motivation at work.